2020
DOI: 10.1289/ehp5444
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Exposure to Perfluoroalkyl Substances (PFAS) and ADHD: A Meta-Analysis of Nine European Population-Based Studies

Abstract: INTRODUCTION: To date, the evidence for an association between perfluoroalkyl substances (PFAS) exposure and attention deficit and hyperactivity disorder (ADHD) is inconclusive. OBJECTIVE: We investigated the association between early life exposure to perfluorooctane sulfonate (PFOS) and perfluorooctanoic acid (PFOA), and ADHD in a collaborative study including nine European population-based studies, encompassing 4,826 mother-child pairs. METHODS: Concentrations of PFOS and PFOA were measured in maternal serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 60 publications
(81 reference statements)
3
36
0
2
Order By: Relevance
“…Some studies showed only weak to moderate associations between child's behavior and prenatal PFOA, PFNA, and PFDA exposure (96). A recent investigation of nine European cohorts with a total of 4,826 mother-child pairs found overall no associations between prenatal and early postnatal (up to 24 months of age) PFOS and PFOA exposure and ADHD risk (97). Up to now, only a very recent study by Luo et al addressed the issue of the role of thyroid hormone perturbations as the mechanism through which PFAS would impair neurodevelopment in children (79).…”
Section: Prenatal Exposure To Pfas: Effects On Maternal and Neonatal Thyroid Functionmentioning
confidence: 99%
“…Some studies showed only weak to moderate associations between child's behavior and prenatal PFOA, PFNA, and PFDA exposure (96). A recent investigation of nine European cohorts with a total of 4,826 mother-child pairs found overall no associations between prenatal and early postnatal (up to 24 months of age) PFOS and PFOA exposure and ADHD risk (97). Up to now, only a very recent study by Luo et al addressed the issue of the role of thyroid hormone perturbations as the mechanism through which PFAS would impair neurodevelopment in children (79).…”
Section: Prenatal Exposure To Pfas: Effects On Maternal and Neonatal Thyroid Functionmentioning
confidence: 99%
“…Early life exposure to PFASs in human milk has been correlated in 2020 to different negative outcomes in infants, although further studies are necessary to confirm the first and so far weak evidence from very few studies [ 183 ]. A European-based meta-analysis including more than 4800 mother–child dyads suggested an increased prevalence of attention-deficit/hyperactivity disorder (ADHD) linked to PFAS exposure in girls, in children from nulliparous women and in children from low-educated mothers [ 183 ]. A small Chinese cohort of 174 mother-infant pairs correlated PFAS exposure via human milk and negative outcomes in postnatal growth, particularly infants’ length and weight gain rates [ 127 ].…”
Section: Environmental and Dietary Contaminantsmentioning
confidence: 99%
“…These chemicals pass through the placenta and can affect the developing fetus [ 13 , 14 ], leading to adverse birth outcomes [ 15 , 16 , 17 ]. Prenatal exposure to PFAS and non-chemical stressors also has been linked to impaired cognition in childhood [ 10 , 18 , 19 ]. However, these associations have been inconsistent across study populations.…”
Section: Introductionmentioning
confidence: 99%